(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
The experiment was carried out at Agricultural Research Field, Noakhali Science and Technology University, Noakhali, Bangladesh during the period from November 2021 to March 2022, to observe the effect of nitrogen (N), phosphorus (P) and potassium (k) fertilizer on growth and yield of garlic (Allium sativum L. V: BINA Roshun-1). The experiment was laid out in a Randomized Complete Block Design (RCBD) comprising four treatments with three replications. The treatments were T0 (no NPK), T1 (NPK 70-70-100 kg ha-1), T2 (NPK 100-100-140 kg ha-1), T3 (NPK 130-130-180 kg ha-1), and here, N = Nitrogen, P=P2O5, K= K2O respectively. Data were recorded from harvesting stages of plant growth on the plant height, number of leaves per plant, leaf length, number of roots per plant, bulb diameter, bulb length, number of cloves per plant, whole weight of plant, fresh weight of bulb and fresh bulb yield per hectare. All the recorded parameters were statistically significant (p<0.01). The highest plant height (69.57 cm) was recorded from T3 (NPK 130-130-180 kg ha-1) whereas the lowest plant height (51.40 cm) was obtained from the control T0 (no NPK). The maximum number of leaves per plant (9.97), leaf length (38.10 cm), number of roots per plant (90.83), bulb length (3.30 cm), bulb diameter (3.80 cm), number of cloves per plant (28.97), whole weight of plant (65.07 g), fresh weight of bulb (42.50 g) and fresh bulb yield per hectare (2.83 t/ha) was found in treatment T3 (NPK 130-130-180 kg ha-1) whereas lowest data recorded from control T0 (no NPK). Observing the results, it can be stated that application of NPK fertilizer @ N 130 kg ha-1, P2O5 130 kg ha-1 and K2O 180 kg ha-1 for garlic cultivation gave better growth and yield in the coastal zone of Bangladesh. Res. Agric. Livest. Fish. 10(1): 53-60